Clinical evaluation of temporomandibular joint disorders among dental students at the University of Science and Technology, Sanaa, Yemen - Al-Dailami, Abdulwahab; Al-Badany, Najwa; Al-Jawfi, Khaled; Al-Hadi, Yahya; Al-Hudaid, Ali; Shamala, Anas (Medknow Publication, 2020)
Aim and Objectives: The study was designed to evaluate the temporomandibular joint disorders among dental students at the University of Science and Technology (UST). Subjects and Methods: The sample size included 267 dental students in UST aged between 18 and 27 years. The study was based on Fonseca's anamnestic index and its questionnaire, which was composed of 10 questions and an examination sheet composed of demographic data and clinical examination. Results: Of 267 students, 178 of them were female (66.7%) and 89 of them were male (33.3%). 52.1% of the study participants were with no temporomandibular disorders (TMDs), 37.5% with mild TMDs, 9.7% with moderate TMDs, and 0.7% with severe TMDs. Regarding clinical examination findings, 81.7% of the study participants were with normal mouth opening and 18.3% were with limited mouth opening. The participants with or without tenderness during palpation were 13.1% and 86.9%, respectively. Positive participants with auscultation (clicking) were 45.3% and 54.7% were negative participants. Conclusion: The mild TMDs were most common, then moderate TMDs were less common, and severe TMDs were rarely. The females were more affected. History of the past dental treatment and psychological stress was found in students having TMDs.